Analysis the Gap Between BNM Regulation and MM Application in Islamic Banking - Rahman, Audia Syafaatur (European Journal of Islamic Finance, 2017)
Bank Negara Malaysia resolved the utilization of Musharakah Mutanaqisah on the Shariah Advisory Committee 56th meeting in 2010. In the practice, most of the bank use Musharakah Mutanaqisah for the home financing purpose. This study examines the gap between the BNM regulation and both the Maybank Islamic and HSBC Amanah practices. The method of analysis is using qualitative study based on the library research. The result has found the gaps which consist of one major gap and three minor gaps, the major gap is related to charging early settlement fee by HSBC Amanah. In addition, three minor gaps are related to wa’d statement in both banks, pledge statement in Maybank side, and default approach compliance in both banks. However, this study does not examine the gap that related to the contract validity. Nevertheless, one single gap found might create the serious issue that leads to effect the contract validity of the product. By uncovering one gap that existed in their practices, this study suggests for better monitoring and supervision conducted by all involved parties. BNM Shariah Advisory Council and Respective Islamic Bank committee should verify the practice that may cause the contract to become void. In addition, the Islamic Financial Institutions should strictly follow all the regulation issued by the Bank Negara Malaysia in all their practices and publication in order to make the contracts acceptable according to Shariah and to cater public confidence. Adhering to guidelines along with the sharia standard of the product further increases accountability and trustworthy of sharia compliancy in particular product.